Case Report: HLA-DRB1 04:01 found in a child with adenovirus type 2 -linked hepatitis - Katsumi, Yoshiki; Nishimura, Yui; Goto, Sachiko; Ozawa, Seiichiro; Nishiura, Tomoko; Kotera, Akira; Kawahara, Yoshiyuki; Higashikawa, Shiori; Iwasaki, Rina; Toriiminami, Yutaka; Asai, Norio; Fujita, Naohisa (Frontiers in Immunology, 2025)
Since 2022, cases of hepatitis of unknown origin have been reported in children worldwide. Adeno-associated virus type 2 (AAV2) was identified as a cause, with most affected children having the HLA-DRB1 04:01 genotype. In this study, we hypothesized that HLA-DRB1 04:01 in the host may also be a potential predisposing factor of acute hepatitis caused by other viruses. We report a case that met the definition of severe hepatitis of unknown cause in a child; adenovirus type 2 (AV2) was detected in her specimens. The patient was a 1-year-old girl who visited a doctor because of fever occurring 1–2 days per week, respiratory symptoms, and diarrhea. One month later, the patient was referred to our hospital because of prolonged elevated liver enzyme concentrations. Two weeks after the initial visit, her aspartate aminotransferase (AST) and alanine aminotransferase (ALT) concentrations increased to 1558 and 1843 IU/L, respectively. The patient’s liver enzyme concentrations decreased markedly with only observation and intravenous hydration during hospitalization within a few days. Thereafter, hepatic enzymes were transiently elevated with each common cold, but all recovered spontaneously. The adenovirus (AV) antibody levels increased substantially 2 weeks after admission. The patient’s human leukocyte antigen (HLA) was determined to be of the DRB1 04:01 genotype. The presence of HLA-DRB1 04:01 is consistent with that reported in pediatric patients with AAV2 hepatitis in the United Kingdom, indicating that it may have been involved in the host immune response and acute hepatitis in this child. HLA-DRB1 04:01 may predispose children to acute hepatitis from various viruses, including AV2, AAV2, and possibly respiratory viruses, which requires clinical attention.